Determination of Intent of Purchase of Environmentally Friendly Packaging Products to Students in Jambi City - Pranata, Herry Sofyandy; Khairinal, Khairinal; Suratno, Suratno; Rosmiati, Rosmiati (PPSDP International Journal of Education, 2023)
The impact of environmental-based attitudes, norms, and education on the intention to buy environmentally friendly packaging products. So from that, this study aims to explore structural models of how attitude variables, norms, and environmental-based education contribute to the intention to buy environmentally friendly packaging. The author uses a quantitative approach and data collection method with a Google survey of 300 students in the city of Jambi. Application of the theory of planned behavior and its expansion by adding an environmental-based educational construction to the intention of purchasing environmentally friendly packaging products.